AINTEGUMENTA and AINTEGUMENTA-LIKE6/PLETHORA3 Induce LEAFY Expression in Response to Auxin to Promote the Onset of Flower Formation in Arabidopsis . Issue 1 (4th November 2015) - Yamaguchi, Nobutoshi; Jeong, Cheol Woong; Nole-Wilson, Staci; Krizek, Beth A.; Wagner, Doris
Abstract : Two parallel pathways confer floral identity on developing lateral primordia downstream of auxin. Abstract: Proper timing of the onset to flower formation is critical for reproductive success. Monocarpic plants like Arabidopsis ( Arabidopsis thaliana ) switch from production of branches in the axils of leaves to that of flowers once in their lifecycle, during the meristem identity transition. The plant-specific transcription factor LEAFY (LFY) is necessary and sufficient for this transition. Previously, we reported that the plant hormone auxin induces LFY expression through AUXIN RESPONSE FACTOR5/MONOPTEROS (ARF5/MP). It is not known whether MP is solely responsible for auxin-directed transcriptional activation of LFY . Here, we show that two transcription factors belonging to the AINTEGUMENTA-LIKE/PLETHORA family, AINTEGUMENTA (ANT) and AINTEGUMENTA-LIKE6/PLETHORA3 (AIL6/PLT3), act in parallel with MP to upregulate LFY in response to auxin. ant ail6 mutants display a delay in the meristem identity transition and in LFY induction. ANT and AIL6/PLT3 are expressed prior to LFY and bind to the LFY promoter to control LFY mRNA accumulation. Genetic and promoter/reporter studies suggest that ANT/AIL6 act in parallel with MP to promote LFY induction in response to auxin sensing. Our study highlights the importance of two separate auxin-controlled pathways in the meristem identity transition.